SURVEI KELENGKAPAN SARPRAS PEMBELAJARAN PENJAS PADA SMA/SEDERAJAT SE-KECAMATAN SERUYAN HILIR KABUPATEN SERUYAN - Surini (Jurnal Keolahragaan JUARA, 2021)
This research is motivated by the limited facilities and infrastructure for Physical Education for Senior High Schools/Equivalents in Seruyan Hilir District, Seruyan Hilir Regency. This study aims to determine the completeness of the facilities and infrastructure for high school/equivalent physical education in Seruyan Hilir District, Seruyan Hilir Regency. This research is a descriptive quantitative research with survey method. The data collection technique is direct observation in the field and the data results are entered into the observation sheet. The population of this research is SMA/equivalent in Seruyan Hilir Subdistrict, Seruyan Hilir Regency, totaling 4 schools. All schools are used as research objects so that this research can be stated as a population study. Based on research on the survey of physical education facilities and infrastructure for SMA/equivalent in Seruyan Hilir District, Seruyan Hilir Regency, it was concluded that the category was sufficient for 3 schools and the category for lacking was 1 school.